The Influence of Complementary Feeding Education by Midwives on the Variation of Complementary Feeding in Infants - Bety Mayasari; Puspita Sari Pribadi; Hayatul Rahimah; Rahmaini Fitri Harahap; Sari Ida Miharti (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Complementary feeding (MP-ASI) is essential for supporting infant growth and development. However, inappropriate complementary feeding practices remain common due to mothers’ limited knowledge. Education provided by health workers, particularly midwives, is expected to improve maternal knowledge and promote more diverse complementary feeding practices. This study aimed to examine the effect of complementary feeding education by midwives on the diversity of complementary feeding among infants. A quantitative pre-experimental one-group pretest–posttest design was conducted at Air Dingin Health Center, Padang. Thirty mothers with infants aged 6–12 months were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected through pretest and posttest questionnaires before and after health education. Maternal knowledge was assessed using structured questionnaires, while complementary feeding diversity was evaluated following the intervention. Data were analyzed using descriptive statistics and paired t-tests with a significance level of p < 0.05. Before the intervention, 60% of mothers had low knowledge, 30% moderate, and 10% good knowledge. After education, 50% demonstrated good knowledge, 40% moderate, and 10% low knowledge. The proportion of mothers providing diverse complementary foods increased from 30% to 70%. Statistical analysis showed significant improvements in both maternal knowledge and complementary feeding diversity (p < 0.05). Midwife-led complementary feeding education effectively enhances maternal knowledge and complementary feeding practices.